Attenuated niacin-induced skin flush response in individuals with clinical high risk for psychosis. Issue 2 (25th April 2022) - Gan, Ranpiao; Wei, Yanyan; Wu, Guisen; Zeng, Jiahui; Hu, Yegang; Xu, Lihua; Tang, Xiaochen; Liu, Xiaohua; Liu, Haichun; Chen, Tao; Wang, Jijun; Zhang, Tianhong
Abstract : Background: Impaired sensitivity of the skin flush response to niacin is one of the most replicated findings in patients with schizophrenia. However, prior studies have usually focused on postonset psychosis, and little is known about the clinical high-risk (CHR) phase of niacin sensitivity in psychosis. Aims: To profile and compare the niacin flush response among CHR individuals (converters and non-converters), patients with first-episode schizophrenia (FES) and healthy controls (HCs). Methods: Sensitivity to four concentrations (0.1–0.0001 M) of aqueous methylnicotinate was tested in 105 CHR individuals, 57 patients with FES and 52 HCs. CHR individuals were further grouped as converters and non-converters according to the 2-year follow-up outcomes. Skin flush response scores were rated on a 4-point scale. Results: Of the 105 CHR individuals, 21 individuals were lost during the study, leaving 84 CHR individuals; 16 (19.0%) converted to full psychosis at 2 years of follow-up. Flush response scores identified in the CHR samples were characterised as modest degree levels, intermediate between those of HC individuals and patients with FES. The flush responses in the CHR group mimicked the responses observed in the FES group at higher concentrations (0.01 M, 0.1 M) and longer time points (15 min, 20 min); however, these became comparable with the responses in the HC group at the shorter time points and at lower concentrations. The converters exhibited lower mean flush response scores than the non-converters. Conclusions: Attenuated niacin-induced flushing emerged during the early phase of psychosis. New devices should be developed and verified for objective quantification of skin responses in the CHR population.